Job opportunities for whom? Labour market dynamics and service sector employment growth in Germany and Britain - Fagan, Colette; O'Reilly, Jacqueline; Halpin, Brendan (Berlin, 2005)
"This report examines structural change in employment and the development of servicesector jobs in Germany and Britain between 1993 and 2002. During this period the British labour market was buoyant, while the employment situation in Germany can only be described as dismal. There is much political interest in the potential for creating new jobs in the service sector. But these developments raise a number of controversial issues when this involves the potential expansion of low-skill, low-wage service jobs, especially in a country such as Germany which has traditionally enjoyed a high-skill, high-wage equilibrium."